1963
DOI: 10.1530/jrf.0.0050423
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and the Accomplishment of Parturition in the Sheep

Abstract: Summary. A flock of thirty ewes was observed through two pregnancies to determine whether parturition could be delayed by the systemic administration of gestagens. In the first season, the four treated groups received daily injections of 2-5 and 10 mg, 6a-methyl-17a-hydroxyprogesterone acetate (6-map) and 10 and 40 mg progesterone for 14 days starting 1 week before the expected date of delivery. The time and course of delivery appeared to be unaffected. The following season the dose levels were increased to 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…unless supraphysiological doses of progesterone were administered. Although administration of progesterone has also been shown $49 delay or prevent prematurely induced or normal parturition in cattle and swine as well as in sheep (Bengtsson and Schofield 1963;Nellor 1963; J6chle ~t a / . 1972; Fairclough et al %984), an increased incidence of distocia and fetal death whs reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…unless supraphysiological doses of progesterone were administered. Although administration of progesterone has also been shown $49 delay or prevent prematurely induced or normal parturition in cattle and swine as well as in sheep (Bengtsson and Schofield 1963;Nellor 1963; J6chle ~t a / . 1972; Fairclough et al %984), an increased incidence of distocia and fetal death whs reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the sheep, administration of progesterone during late pregnancy, when given in physiological doses of 80 mg/day for a week at around the time of parturition (Bengtsson and Schofield 1963) or BOO mg for 4 days during a fetal infusion of dexamethazone QLiggins et ad. 1972), failed to delay noma% or dexarnethazone-induced parturition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In normal pregnancy the placenta transports nutrients from the mother to the fetus and synthesizes a high amount of progesterone which regulates pregnancy (10,11). The weight of fetal rat adrenal glands, plasma corticoste rone level and adrenal corticosteroid synthesis in vitro from 4-14C-progesterone increased from the 17th to the 21st day of pregnancy and quickly decreased on the 22nd day of preg nancy (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous progesterone did not delay the onset of labor in the ewe (Bengtsson and Schofield, 1963;Liggins e;t aJ^. , 1972) but it sometimes caused a protracted delivery.…”
Section: Dxms -3 Rturitionmentioning
confidence: 97%